Breast Thermography. Indications y technique - Mate, Miguel; Laviña, Raúl; Pressa, Carlos; Pérez Penco, Ernesto; del Campo, Alberto; Albo, Manuel (Cirugía del Uruguay, 1983)
This work analizes mamary termography, sets its indications in diagnosis of mamary diseases and evalues the physicochemistry and biologic bases of this procedure. Remarks the method 's val u e in arder. to register a point (termogenesis) not available by any pther way of study. Places its pronostica! range and signals its other benefits: control possibilities and massive studies. Describes methodology and tec,11tlic' of contact mamary termography (in plate).